Determinants of subjective and objective burden of informal caregiving of patients with psychotic disorders. (November 2015) - Flyckt, Lena; Fatouros-Bergman, Helena; Koernig, Thomas
Background: In a previous study, the objective burden of informal caregiving to patients with psychotic disorders amounted to 22 hours/week, and the subjective burden was huge with predominately anxiety and depression as main symptoms. In this study, determinants of the informal caregiving burden are analyzed to find foci for interventions to ease the size of burden. Methods: Patients with psychotic disorders ( n  = 107) and their informal caregivers ( n  = 118) were included. They were assessed with a comprehensive battery of rating scales including patient and caregiver characteristics as well as the amount and quality of health-care provision. Results: A multiple linear regression analysis showed that the subjective burden was significantly lower when patients had higher levels of functioning and when the health status of the informal caregivers was good. No significant determinants were found for the objective burden, but an association was found between a higher socioeconomic status of the caregivers and the amount of money provided for the patient. An association was also found between a positive perception of caregiving and more hours spent on caregiving. Conclusion: The functioning level of the patients was the main determinant of the subjective burden of informal care. For the objective burden, no main determinant was found.